An Analysis of Physician Behaviors During the Holocaust: Modern Day Relevances - Miller, Susan Maria; Gallin, Stacy (Conatus - Journal of Philosophy, 2019)
Even with the passage of time, the misguided motivations of highly educated, physician-participants in the genocide known as the Holocaust remain inexplicable and opaque. Typically, the physician-patient relationship inherent within the practice of medicine, has been rooted in the partnership between individuals. However, under the Third Reich, this covenant between a physician and patient was displaced by a public health agenda that was grounded in the scientific theory of eugenics and which served the needs of a polarized political system that relied on this hypothesis to justify society’s racial hygiene laws. As part of the National Socialist propaganda, Adolf Hitler ominously argued that the cultural decline of Germany after World War I could largely be based on interbreeding and a “resultant drop in the racial level.” This foundational premise defined those who could be ostracized, labeled and persecuted by society, including those who were assimilated. The indoctrination and implementation of this distorted social policy required the early and sustained cooperation and leadership of the medical profession. Because National Socialism promised it could restore Germany’s power, honor and dignity, physicians embraced their special role in the repair of the state. This article will explore the imperative role, moral risks and deliberate actions of physicians who participated in the amplification process from “euthanasia” to systemic murder to medically-sanctioned genocide. A goal of this analysis will be to explore what perils today’s physicians would face if they were to experience the transitional and collective behaviors of a corrupted medical profession, or if they would, instead, have the fortitude and courage necessary to protect themselves against this collaboration. Our premise is that an awareness of history can serve as a safeguard to the conceit of political ascendency and discrimination.